O ensino e a aprendizagem da leitura sobre as questões étnico-raciais: dilema, problema ou construção de conhecimentos desejáveis? - Oliveira, Silvia Christina Monteiro de (2013)
The present dissertation aims at questioning how teachers and students construct their ethnic/racial issues in the classroom through reading. The thesis focuses on the study of reading and interpretation of the rap in the form of Caetano Veloso poem, Slave Ship, and aims to contribute to the development of text reading and understanding. Moreover, it reflects on the situation of the students of African descent, seeking to reflect on the importance of the enforcement of law number 10.639.909/ 2003 at schools. As the type of text worked out in the research is literary and has many metaphors, and a large fraction of the public schools do not prepare their students for the skills and competencies needed in this kind of reading, I support the Cultural-Historical Theory (Vygotsky, 1934) and point out the importance of this support when it comes to reading as a social practice. Regarding methodological procedures, action research (Thiollent, 1982) was developed under a qualitative approach and was aimed at analyzing the actions of a teacher of Portuguese and her students over three reading classes. The instrument used for data generation was the recording of classes in which there was the "thinking together" process (Pontecorvo, 2005). The categories of linguistic analysis are proposed by Orsolini (2005), Pontecorvo (2005) and Kebrat Orechioni (2006). In data analysis I sought to discuss the pedagogical actions in the classroom in order to understand how teachers and students construct their ethnic/racial issues in reading lessons. The survey results allow to say that the actions of the researcher teacher - the practice of mediation and reading interaction- enabled the development of students as critical and reflective readers, and there was an appreciation of Afro-Brazilian Culture and History. Finally, this research allowed the researcher teacher to think about possible affirmative pedagogic action around the blackness in order to propose a school prepared to recognize and assimilate the diversity in school life and to provide students the opportunity to reflect critically on the ethnic/racial issues in the classroom